Surface runoff of rainfall in an experimental plantation of macaúba palm (Acrocomia aculeata) under different forms of management - Corrêa, João Batista Lúcio; Dias, Herly Carlos Teixeira; Tonello, Kelly Cristina; Cicco, Valdir de; Silva, Elias; Silveira, Lucas Jesus da; Sato, Aurora Yoshiko (Revista Árvore, 2018)
Several studies have been conducted aiming to explore the commercial potential of the macaúba palm. However, research on the hydrological processes of this crop are scarce. Thus, we aimed to quantify the surface runoff in a macaúba plantation subjected to different crop management techniques, from September 2012 toAugust 2013. We established 10 plots for surface runoff quantification; each plot had a 63-m² area, was delimited by metallic foils and had a gallon to collect runoff water at its outlet. Plots consisted of three treatments and three repetitions, plus one control plot, each having four macaúba plants. Treatments were as follows: treatment one (T1) - with no soil conservation technique being implemented; treatment two (T2) - with a narrow-base terrace 40 cm wide and 30 cm deep; treatment three (T3) - with bean being planted during the rainy months, forming vegetation strips; and control treatment (T0) - with no macaúba plants, with spontaneous vegetation growing throughout the entire plot and with no soil conservation technique being implemented. Surface runoff differed among treatments. T2 was the treatment with lowest runoff and also the one that demanded the highest precipitation volume for surface runoff to occur. Our results indicate that both the cover and the use of soil conservation techniques are closely related to surface runoff, which in turn affects the occurrence of erosion and infiltration.

Diversos estudos têm sido conduzidos com o objetivo de se conhecer as potencialidades comerciais da macaúba. Contudo, há escassez de estudos sobre os processos hidrológicos dessa cultura. Assim, este estudo teve por objetivo quantificar o escoamento superficial no plantio de macaúba, sob influência de diferentes técnicas de manejo da cultura, no período de setembro de 2012 até agosto de 2013. Foram instaladas dez parcelas de quantificação do escoamento superficial com área 63 m2 cada, delimitadas com lâminas metálicas e, na saída de cada parcela, galões para coleta da água de escoamento. As parcelas constituíram três tratamentos com três repetições, e parcela testemunha, cada uma envolvendo quatro (4) plantas de macaúba. No tratamento um (T1) sem técnicas de conservação do solo; o tratamento dois (T2): cordão de contorno com 40 cm centímetros de largura por 30 cm de profundidade; o tratamento três (T3): durante os meses chuvosos com plantio de feijão em faixas; o tratamento testemunha (T0): sem plantas de macaúba, com a vegetação espontânea crescendo por toda a parcela, onde não foi usada nenhuma técnica de conservação de solo. O escoamento superficial se comportou de maneira diferente entreostratamentos. T2 apresentoumenores valoresdeescoamentosuperficial,sendo, também,o tratamento no qual o escoamento superficial exigiu maior volume de precipitação para que se iniciasse. Os resultados indicam que tanto a cobertura como o uso detécnicas de conservação do solo estão intimamente relacionadas com o processo de escoamento superficial, que por sua vez, terá influência em processos erosivos e à infiltração.
Keywords: Forest hydrology; Soil erosion; Infiltration